Does gender diversity mediate the relationships of diversity beliefs and workplace happiness? - Islam, Shafiqul; Alam, Md. Jahangir; Penalba, Maileenita (Frontiers in Sociology, 2024)
Though its intensity varies across cultures, practicing diversity beliefs has become increasingly prevalent in contemporary business organizations. Traditionally, diversity encompasses various aspects such as gender, education, religion, language, age, ethnicity, culture and personality orientation. The current study has demonstrated to identify the mediating effects of gender diversity on diversity beliefs and workplace happiness. The targeted population is made up of full-time Bangladeshi employees working in both public and private organizations. The researchers distributed a questionnaire to 500 employees and obtained 320 valid responses, resulting in a response rate of 64%. The study used the Structural Equation Modelling (SEM) technique to assess the mediating effects and direct effects among the variables. The results demonstrate that gender diversity significantly mediate the associations between diversity beliefs and workplace happiness. This means that employees are more likely to be happy with their jobs if the workplace reflects gender variety in its workforce. The study further demonstrates that workplace happiness significantly affects employees’ job satisfaction, engagement and commitment. The present research foregrounds that firms and concerned authorities must increase their various attempts to establish gender-equal policies that appear to be more effective for diversity practice and workplace happiness in work organizations.